Design and Development of Real Time ECG Monitoring System - Rabiya Begum Mohd. Saleem, Ramesh R. Manza (International Journal of Advanced Science and Technology, 2020)
ECG monitoring system is the vital and very important medical tool used for monitoring the person’s cardiac health; it is non invasive and painless procedure. This paper aimed to describe the Real time ECG monitoring system designed and developed using microcontroller. The designed system is a portable device having a small analog front end circuit, a microcontroller unit, a display and storage unit and software designed in MATLAB for Analysis of the ECG signals. The major goal of the work is to develop a prototype which is easy to use, portable, having very less cost and accurate. The proposed system acquires the signals using electrodes placed on the surface of the skin and display these real time signals on LCD screen with its heart rate. The device is also equipped with a memory card that stores a person’s ECG data for analysis in MATLAB.